2003
DOI: 10.1007/s10201-003-0106-1
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and depuration of microcystin produced by the cyanobacterium Microcystis in a freshwater snail

Abstract: Seasonal changes in microcystin concentrations in a resident snail (Sinotaia histrica) and an edible clam (Corbicula sandai) in Lake Biwa were surveyed. To clarify both the accumulation and depuration of microcystins, experimental studies with microcystin were also carried out on the snail. In the field investigation, microcystin was detected from the hepatopancreas and intestine of S. histrica (up to 3.2 µg g Ϫ1 dry weight and 19.5 µgg Ϫ1 dry weight, respectively); however, no microcystin was detected in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 41 publications
2
47
2
2
Order By: Relevance
“…Investigations on a resident snail [Sinotaia histrica (Gould, 1859)] for Lake Suwa (Japan) showed that the concentrations of MCs were significantly higher in digestive tracts than in the hepatopancreas (Ozawa et al, 2003;Xie et al, 2007), but was different from the pattern of another prosobranchia species [Bellamya aeruginosa (Reeve, 1863)] in two subtropical plain lakes (Lakes Caohu and Taihu). These studies of B. aeruginosa showed that concentrations of MCs in the hepatopancereas were not only significantly higher than those in digestive tracts, but also showed positive correlations with each other Zhang et al, 2007Zhang et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigations on a resident snail [Sinotaia histrica (Gould, 1859)] for Lake Suwa (Japan) showed that the concentrations of MCs were significantly higher in digestive tracts than in the hepatopancreas (Ozawa et al, 2003;Xie et al, 2007), but was different from the pattern of another prosobranchia species [Bellamya aeruginosa (Reeve, 1863)] in two subtropical plain lakes (Lakes Caohu and Taihu). These studies of B. aeruginosa showed that concentrations of MCs in the hepatopancereas were not only significantly higher than those in digestive tracts, but also showed positive correlations with each other Zhang et al, 2007Zhang et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, MCs not only promote the development of primary liver cancer (Sekijima et al, 1999), but also initiate liver tumors (Ito et al, 1997). Moreover, MCs can be transferred through food chains/webs by bioaccumulation in various organisms including zooplankton, mussels, snails, shrimp, fish and even turtles, ducks, and other waterfowl (Amorim and Vasconcelos, 1999;Ozawa et al, 2003;Lance et al, 2006;Xie et al, 2007;Chen et al, 2009;Martins and Vasconcelos, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations